South Africa Mobilises: The First Five Months of the War - Samson, Anne (Scientia Militaria - South African Journal of Military Studies, 2016)
When war broke out in August 1914, the Union of South Africa found itself unprepared for what lay ahead. When the Imperial garrison left the Union during September 1914, supplies, equipment and a working knowledge of British military procedures reduced considerably. South Africa was, in effect, left starting from scratch. Yet, within five months and despite having to quell a rebellion, the Union was able to field an expeditionary force to invade German South West Africa and within a year agree to send forces to Europe and East Africa. This article explores how the Union Defence Force came of age in 1914.